CATS Design: A Context-Aware Test Suite Design Process - Rodrigues, Felyppe; Matalonga, Santiago; Travassos, Guilherme H. (Anais do Simpósio Brasileiro de Testes de Software Sistemático e Automatizado (SAST); 2016: Anais do I Simpósio Brasileiro de Testes de Software Sistemático e Automatizado, 2016)
Context-awareness is the ability of a system to gather information from its context and adapt its behaviors. This feature makes the testing of Context-aware software systems more challenging. Based on this assumption, this research proposes an approach to design functional test cases for context-aware software systems, the CATS Design. In its development, ideas from other domains presenting similar issues were tailored to the problem of testing context-aware software systems. This paper presents the design process of CATS Design, and its two empirical evaluation stages: 1) through a proof of concept, and 2) with an observational study involving eight undergraduate students in Uruguay. The results suggest that it is feasible to apply CATS Design for designing test cases for context-aware software systems.